(untitled) (Quest Journal of Management and Social Sciences, 2025)
Background: Ride-sharing services have emerged as an alternative mode of urban transportation in Kathmandu Valley, aiming to address issues such as traffic congestion and limited public transport options. However, user satisfaction with these services remains uncertain due to varying service quality and operational challenges. Purpose: The purpose of the study is to assess the user’s satisfaction with the ride-sharing service in Kathmandu Valley. Specifically, the study assesses the current status of ride-sharing services in the Kathmandu Valley to examine the impact of service quality on user satisfaction with ride-sharing services in the Kathmandu Valley, to identify the various challenges faced by ride-sharing services, and to propose potential solutions to address these challenges. Design/methodology/approach: This study adopted an explanatory research design. Expectation confirmation theory (ECT) is used for the study because SERVQUAL is based on the expectancy-disconfirmation paradigm, which states that service quality is defined as the degree to which consumers’ pre-consumption expectations of quality are confirmed or contradicted by their actual perception of the service experience. The primary data for this study were collected from 417 respondents, using a non-probability convenience sampling method. Structured questions were administered through the KOBO toolbox to gather the necessary information. The collected data were then analyzed using descriptive and inferential statistics in MS Excel and SmartPLS 4.0. Findings: Tangibility, reliability, responsiveness, and empathy directly influence users’ satisfaction in using ride-sharing services in the Kathmandu Valley; however, assurance had no direct influence on users’ satisfaction. In the context of using ride-sharing services, Nepali customers are not yet accustomed to using ride-sharing services compared to developed countries. Besides, the major challenges faced by ride-sharing service users include long wait times, safety concerns, unavailability of rides, unfriendly or unprofessional driver behavior, pricing issues, vehicle cleanliness, payment options, and difficulty using the app. The major solutions to the challenges are short wait times, enhanced safety measures, sufficient ride availability, friendly or professional driver behavior, better pricing models, improved vehicle maintenance, more driver training programs, easy-to-use apps, and more payment options. Conclusion: This study concludes that tangibility, reliability, responsiveness, and empathy have a positive and significant relationship with users’ satisfaction, whereas assurance is insignificantly correlated with user satisfaction. Keywords: Ride-sharing Service, Users’ Satisfaction, SERVQUAL Dimension, Service Quality, Kathmandu Valley